2004
DOI: 10.1146/annurev.publhealth.25.101802.123107
|View full text |Cite
|
Sign up to set email alerts
|

Assuring the Health of Immigrants: What the Leading Health Indicators Tell Us

Abstract: Over the past 20 years, the United States has experienced one of the largest waves of immigration in its history. Understanding the health status and needs of immigrants is important because of their growing numbers and their contribution to the health of the nation, but it is challenging because of gaps in national databases, the heterogeneity of immigrant populations, and uncertainty about how migration affects health. Healthy People 2010 outlines the nation's public health objectives for the current decade.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
139
0
15

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(161 citation statements)
references
References 99 publications
7
139
0
15
Order By: Relevance
“…Key themes to emerge from that body of work suggest that many immigrants, but not all, experience worsening health outcomes with greater amounts of time in the USA 12,38,39 . Our results also indicate that undocumented immigrants who have lived in the USA for longer periods of time report poorer health outcomes, although it is not yet clear why this is the case.…”
Section: Discussionmentioning
confidence: 99%
“…Key themes to emerge from that body of work suggest that many immigrants, but not all, experience worsening health outcomes with greater amounts of time in the USA 12,38,39 . Our results also indicate that undocumented immigrants who have lived in the USA for longer periods of time report poorer health outcomes, although it is not yet clear why this is the case.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 In general, population studies find that the health of immigrants tends to be better than that of the general population in both the sending and receiving countries. 24,25 Immigrants to Canada often show slightly lower rates of mental disorders than the general population. 26,27 The 2000-2001 Canadian Community Health Survey found that newly arrived immigrants (length of residence less than one to four years) had the lowest rates of depression (odds ratio [OR] 0.33, 95% confidence interval [CI] 0.26-0.41) and alcohol dependence (OR 0.05, 95% CI 0.02-0.12) compared with the Canadian-born population.…”
Section: How Does Migration Affect Mental Health?mentioning
confidence: 99%
“…The health service professional often has never had specific training nor has been provided with tools to tackle the abovementioned issues, that are as basic as understanding health data with regard to ethnicity [22,38]. In particular, very few academic curricula include training future providers about migrant health decline.…”
Section: The Inter-cultural Context Between Provider and Health Servimentioning
confidence: 99%